Optimizing the Use of Phase Change Material Vests Worn During Explosives Ordnance Disposal Operations in Hot Conditions - Davey, Sarah Lee; Lee, Ben James; Smith, Mark; Oldroyd, Mark; Thake, Charles Doug (Frontiers in Physiology, 2020)
Phase change material (PCM) cooling garments’ efficacy is limited by the duration of cooling provided. The purpose of this study was to evaluate the effect of replacing a PCM vest during a rest period on physiological and perceptual responses during explosive ordnance disposal (EOD) related activity. Six non-heat acclimated males undertook three trials (consisting of 2×3×16.5 minute activity cycles interspersed with one 10 minute rest period) in 40 °C, 12% relative humidity whilst wearing a ≈38 kg EOD suit. Participants did not wear a PCM cooling vest (NoPCM); wore one PCM vest throughout (PCM1) or changed the PCM vest in the 10 minute rest period (PCM2). Rectal temperature (Tre), mean skin temperature (Tskin), heart rate (HR), Physiological Strain Index (PSI), ratings of perceived exertion, temperature sensation and thermal comfort were compared at the end of each activity cycle and at the end of the trial. Data displayed as mean [95% CI]. After the rest period, a rise in Tre was attenuated in PCM2 compared to NoPCM and PCM1 (-0.57 [-0.95, -0.20] °C and -0.46 [-0.81, -0.11] °C, respectively). A rise in HR and Tskin was also attenuated in PCM2 compared to NoPCM and PCM1 (-23 [-29, -16] beats∙min-1 and -17 [-28, -6.0] beats∙min-1; -0.61 [-1.21, -0.10] °C and -0.89 [-1.37, -0.42] °C, respectively). Resulting in PSI being lower in PCM2 compared to NoPCM and PCM1 (-2.2 [-3.1, -1.4] and –0.8 [-1.3,-0.4], respectively). More favourable perceptions were also observed in PCM2 vs. both NoPCM and PCM1 (p <0.01). Thermal perceptual measures were similar between NoPCM and PCM1 and the rise in Tre after the rest period tended to be greater in PCM1 than NoPCM. These findings suggest that replacing a PCM vest better attenuates rises in both physiological and perceptual strain compared to when a PCM vest is not replaced. Furthermore, not replacing a PCM vest that has exhausted its cooling capacity, can increase the level of heat strain experienced by the wearer.